Manufacturing and Management Paradigms, Methods and Tools for Sustainable Industry 4.0-Oriented Manufacturing Systems - Varela, Leonilde (2022)
In the current Industry 4.0 era (I4.0, for short) [1–3], manufacturing and management (M&M) paradigms, methods and tools should be wisely developed to fulfil sustainability issues, regarding not just economic but also social and environmental concerns by simultaneously fostering organizational efficiency excellence and transformational initiatives, therefore contributing to enduring business results.This Special Issue aims to provide new insights regarding manufacturing or management paradigms (strategies), methods, tools, and practices aligned with the contemporary necessity to create and implement sustainable I4.0 manufacturing systems. Each of the five selected papers of this Special Issue makes a novel contribution to that aim.